The Impact of Regulatory Capital and Bank Characteristics on the Relationship between Bank Competition and Risk Taking in the Banking System - Abdel-Wanis, Eman (Journal of Accounting, Business and Management (JABM), 2021)
This paper explores the association between bank competition, regulatory capital, and bank risk taking in an Egyptian setting and to examine the interaction between bank competition and regulatory capital and their impact on bank risk taking in developing countries like Egypt and also investigate the effect of bank characteristics on the relationship between bank competition and bank risk taking through a sample of 27 Egyptian listed banks during the period 2012-2018 using OLS regression . Results indicated that there is a negative impact of bank competition on the bank risk taking and a positive effect of regulatory capital on bank risk taking in the Egyptian listed banks. Results show that increase regulatory play a vertical role in enhance association between competition and bank risk taking and also, there is a positive impact of bank characteristics like: bank size and divarication on bank risk taking in the Egyptian banks. Results refer to there is no effect of bank type, leverage and profitability to support the relationship between bank competition and risk taking